TANIAN LANJANG Pola Tata Ruang dan Kekerabatan Masyarakat Madura - Sattar, Abdul (Sabda: Jurnal Kajian Kebudayaan, 2015)
This study is intended to describe the meaning of the architectural pattern and family relationship among Madurese society. There are three points that will be discussed in this article. The first, the meaning behind Madurese choice in building their home in tanian lanjang. The second, the vital role of kobhung on the pattern of tanian lanjang. The third, the metamorphosis of tanian lanjang: changable and unchangable pattern. To describe all of these aspects and to know what is really meant by Madurese society, it is extremely needed to be part of this society; living with them for a temporal time is a must. The result of this research consists of three important points. The first, the meaning of house building in tanian lanjang is to present the seniority of the inhabitants. The oldest always stays in the west position and the youngest always stay in the east position. A house also becomes a private place for women and kids. Women are also the inhabitants and the owners of houses. The second, kobhung has a vital role in tanian lanjang. It is used to become the centre of all activities done by men. The third, the existence of tongghuh and kobhung is one of unchangable pattern of tanian lanjang.